PAEONIA EMODI: A THREATENED IMPORTANT MEDICINAL PLANT OF HIGHER HIMALAYAN REGION - Purohit, Vijay Kant; Joshi, Praveen; Chauhan, Jaidev; Prakash, Prem (International Journal of Research -GRANTHAALAYAH, 2021)
Himalaya is well known for its rich biodiversity with respect to medicinal and aromatic plants and Paeonia emodi Wall. ex Royle is one of them locally known as Chandra (family Paeoniaceae). In India, it is distributed in North–West Himalaya from Kashmir to Garhwal-Kumaun regions of Uttarakhand with an altitudinal range of 1800 to 2800 m asl. The whole plant of P. emodi is highly effective for uterine diseases, blood purifier, colic, bilious, backbone ache, headache, dizziness, vomiting, dropsy, epilepsy and hysteria while the seeds are purgative. A present phytosociological study particularly in Garhwal Himalaya, reveals that only few pockets of P. emodi are higher dense in Triyuginarayan and Shyalmi areas (3.80 and 2.72 individual/m2 respectively) while remaining are lower dense under diverse climatic conditions due to invasion by several biotic and abiotic factors. Using available information based on field survey, it assumed that the causes of its degradation are largely overexploitation of immature twigs before flower formation and seed shedding. To conserve the targeted species for future prosperity, Government needs to take immediate and concrete initiatives or imposed the ban on illegal collection or removal of the plant from its natural populations and emphasize the promotion of conservation.